(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Celem opracowania jest analiza pojęć: instrumentalizacji prawa i instrumentalnego użycia prawa, w odniesieniu do wykładni prawa. Tym samym należy zaznaczyć, że przedmiotem artykułu uczyniono jedynie kwestię analizy poszczególnych, wiodących w polskiej teorii prawa, koncepcji interpretacji w zakresie ich podatności na różne formy polityczno-ideologicznego wykorzystania. Artykuł skupia się na refleksji odnośnie tego, jakie cechy tych koncepcji wzmagają albo osłabiają możliwości instrumentalnego potraktowania interpretacji prawniczej. W literaturze przedmiotu najczęściej występuje ograniczenie rozważań jedynie do zjawiska „instrumentalizacji” prawa, głównie – jak się wydaje – w aspekcie jego stanowienia, tj. kodowania norm w sposób jawnie je ideologizujący. Stąd określenie – zamiast instrumentalizacji lub instrumentalnego jego użycia – ideo-logizacji prawa. The paper analyses notions traditionally related to ideologisation of the law in the context of statutory interpretation. Adopting a non-judgemental, positivist scientific approach, the author describes instrumentalisation of the law and instrumental “use” of the law in the view of theoretical concepts pertaining to law interpretation, developed under Polish jurisprudence. Hence the paper aims to outline basic problems with the development of semantics from the perspective of political authority’s “claim” to apply the statutory interpretation that involves certain assumptions resulting from a philosophy of the law and/or philosophy of politics which are treated as the appropriate ones (based on non-juridical criteria). In this respect, it seems crucial to analyse possible configurations of the stages of interpretation process (established and labeled by H. Rabault) as a pre- and overdetermination of the semantics which is the basis for law application decisions.